Medical Updates and Appointment Confirmations: Pet Owners' Perceptions of Current Practices and Preferences - Kogan, Lori; Schoenfeld, Regina; Santi, Stacee (Frontiers in Veterinary Science, 2019)
Pet ownership is increasing, in large part due to the number of millennial pet owners. More pet owners as well as the advent of extensive veterinary care options have resulted in a substantial increase in veterinary care spending. Yet, regardless of client cohort or type of medical procedure performed, communication between clients and veterinarians continues to be a key component in patient care and client satisfaction. Two areas of communication are explored in this study: medical updates to clients when their animals need to stay in the hospital for extended periods of time (at least 4 h) and appointment confirmations. This study, through an anonymous online survey, explored pet owners' stated current modality and frequency of receiving medical updates by their veterinarian and compared these to their stated preferences. Participants' preferences for the modality in which they receive appointment reminders was similarly compared to how they currently receive reminders. There were differences in both frequency (medical updates) and modality (medical updates and appointment confirmations) between what pet owners currently encounter and what they would prefer. In particular, few pet owners receive medical updates or appointment confirmations via text, when a significant portion would prefer this mode of communication. Pet owners also reported wishing to receive medical updates more frequently then they currently experience, with 53.8% of participants reporting they would pay extra for this service. The ramifications of these results are explored with a focus on how to modify these services to best meet the needs of clients.